2006
DOI: 10.1063/1.2263593
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of Shock-Induced Damage for Granite under Dynamic Loading

Abstract: Abstract.Johnson-Holmquist constitutive model for brittle materials, coupled with a crack softening model, is used to describe the deviatoric and tensile crack propagation beneath impact crater in granite. Model constants are determined either directly from static uniaxial strain loading experiments, or indirectly from numerical adjustment. Constants are put into AUTODYN-2D from Century Dynamics to simulate the shock-induced damage in granite targets impacted by projectiles at different velocities. The agreeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Note that some of the excess damage accumulation along the centerline of the calculations is a numerical artifact resulting from the cylindrical symmetry centerline boundary condition. In the copper impact experiment (Figure 2), Ai and Ahrens [2006] observed a hemispherical zone of shear damage of about 4 cm radius, which is similar in shape and size to that produced by the calculation. They also observed radial cracks to depths of about 8 cm.…”
Section: Strength Modelsupporting
confidence: 68%
See 3 more Smart Citations
“…Note that some of the excess damage accumulation along the centerline of the calculations is a numerical artifact resulting from the cylindrical symmetry centerline boundary condition. In the copper impact experiment (Figure 2), Ai and Ahrens [2006] observed a hemispherical zone of shear damage of about 4 cm radius, which is similar in shape and size to that produced by the calculation. They also observed radial cracks to depths of about 8 cm.…”
Section: Strength Modelsupporting
confidence: 68%
“…Next, the strength model is used to simulate laboratory‐scale impact experiments. Ai [2006] and Ai and Ahrens [2006] recently performed a series of laboratory cratering experiments to study shock‐induced damage during impact events. We model three of their laboratory experiments in San Marcos granite: impacts by (1) a 0.64‐cm‐radius copper sphere at 690 m/s (Figure 2); (2) a 3.2‐g lead bullet (3 mm radius) at 1200 m/s (Figure 3); and (3) a 0.64‐cm‐radius lead sphere at 800 m/s (Figure 4).…”
Section: Strength Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…This model has been applied to a number of structural ceramics and it has been observed that the model cannot fully capture both the low‐pressure and the high‐pressure data simultaneously. Figure illustrates the limitations of JH‐2 model in capturing the pressure‐sensitive response of several structural ceramics including boron carbide (B 4 C), silicon carbide (SiC), aluminum nitride (AlN), zirconium diboride–silicon carbide (ZrB 2 –SiC) (M. Shafiq and G. Subhash submitted), float glass, and granite …”
Section: Introductionmentioning
confidence: 99%